Anti-cancer efficacy of novel lonidamine derivatives: Design, synthesis, in vitro, in vivo, and computational studies targeting hexokinase-2 - Ipek, Ozgecan Savlug; Sucu, Bilgesu Onur; Selvi, Saba; Alkan, Fulya Koksalar; Tiryaki, Busra; Alkan, Hilmi Kaan; Sayyah, Ehsan; Tolu, Ilayda; Guzel, Mustafa; Durdagi, Serdar; Ozturk, Nuri; Korkaya, Hasan (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2025)
Targeting cancer metabolism has emerged as an attractive therapeutic strategy in recent years, despite the Warburg effect phenomenon is discovered about a century ago. Based on this phenomenon, cancer cells rely on aerobic glycolysis and require higher rate of glucose consumption compared to normal cells and the hexokinase-2 (HK-2) enzyme catalyzes the first step of glucose metabolism. Consistent with the notion, HK-2 expression is highly elevated in most malignancies and that predicts poor survival in patients. Thus, inhibiting the HK-2 activity may be a potential metabolic target for cancer therapy. Lonidamine (LND) is known as a potential anticancer drug through HK-2 inhibition with varying degrees of efficacy in different malignancies. LND shows potency through voltage-dependent anion channel (VDAC) and HK-2 interaction on mitochondrial membrane. Therefore, we designed and synthesized novel LND analogs to improve its molecular and functional properties. We first performed chemical and structural characterization of these LND analogs and tested their biological activity by in vitro assays and in vivo in mouse xenografts. Among these potent HK-2 inhibitors, Compound 20 was identified as a promising lead compound with anti-tumor activity. Based on the three different cancer cell lines we investigated, our novel LND analogs proved to be more potent than the original molecule. Our findings provide convincing evidence for potentially designing novel analogs of LND and beyond to further improve biological and functional properties existing drugs. Further proven in preclinical settings, our approach may lead to development of more effective therapeutics benefiting patients.
Keywords: Lonidamine; Hexokinase-2 inhibitors; Anti-cancer activity; Glycolysis; Molecular simulations; CANCER; METABOLISM; INITIATION; DISCOVERY; DOCKING; Pharmacology & Pharmacy